Depletion of Alveolar Macrophages Increases Pulmonary Neutrophil Infiltration, Tissue Damage, and Sepsis in a Murine Model of Acinetobacter baumannii Pneumonia - Lee, Hiu Ham (Infect Immun, 2020)
Acinetobacter baumannii has emerged as an important etiological agent of hospital-related infections, especially nosocomial pneumonia. The virulence factors of this bacterium and their interactions with the cells and molecules of the immune system just recently began to be extensively studied. Here, we investigated the impact of alveolar macrophages on A. baumannii pneumonia using a mouse model of infection and a flexible tissue culture system. We hypothesized that depletion of macrophages would enhance sepsis and severity of A. baumannii disease. We showed that macrophages are important for modulating the antibacterial function of neutrophils and play an important role in eradicating A. baumannii infection in vivo. Our findings suggest that in the absence of macrophages in the lungs, A. baumannii replicates significantly, and host proinflammatory cytokines are considerably reduced. Neutrophils are abundantly recruited to pulmonary tissue, releasing high amounts of reactive oxygen species and causing extensive tissue damage. The ability of A. baumannii to form biofilms and resist oxidative stress in the respiratory tract facilitates systemic dissemination and ultimately death of infected C57BL/6 mice. These results provide novel information regarding A. baumannii pathogenesis and may be important for the development of therapies aimed at reducing morbidity and mortality associated with this emerging bacterial pathogen.